Advanced Image Analysis of the Surface Pattern Emerging in Ni3Al Intermetallic Alloys on Anodization - Salerno, Marco; Stępniowski, Wojciech J.; Cieślak, Grzegorz; Norek, Małgorzata; Michalska-Domańska, Marta; Karczewski, Krzysztof; Chilimoniuk, Paulina; Polkowski, Wojciech; Józ´wik, Paweł; Bojar, Zbigniew (Frontiers in Materials, 2016)
Anodization of Ni3Al alloy is of interest in the field of industrial manufacturing, thanks to the formation of protective oxide layer on the materials working in corrosive environments and high temperatures. However, homogeneous surface treatment is paramount for technological applications of this material. The anodization conditions have to be set outside the ranges of corrosion and “burning”, which is the electric field enhanced anodic dissolution of the metal. In order to check against occurrence of these events, proper quantitative means for assessing the surface quality have to be developed and established. We approached this task by advanced analysis of scanning electron microscope images of anodized Ni3Al plates. The anodization was carried out in 0.3 M citric acid at two temperatures of 0 and 30°C and at voltages in the range of 2 12 V. Different figures can be used to characterize the quality of the surface, in terms of uniformity. Here, the concept of regularity ratio spread is used for the first time on surfaces of technological interest. Additionally, the Minkowski parameters have been calculated and their meaning is discussed.